Efficacy of a Copper–Calcium–Hydroxide Solution in Reducing Microbial Plaque on Orthodontic Clear Aligners: A Case Report - Meto, Aida; Colombari, Bruna; Castagnoli, Anna; Sarti, Mario; Denti, Lucia; Blasi, Elisabetta (European journal of dentistry, 2019)
Abstract The aim of this study was to investigate the ability of a copper–calcium–hydroxide-based compound to remove microbial plaque naturally produced onto orthodontic clear aligners. A commercially available dental paste, named Cupral, based on copper–calcium–hydroxide, was used. A healthy volunteer (female, 32 years old), undergoing orthodontic treatment with thermoplastic clear aligners was enrolled. By conventional/confocal microscopy and colony-forming unit (CFU) assay, 2-week used aligners were examined for microbial plaque, prior and following exposure to Cupral. Confocal microscopy revealed abundant plaque irregularly distributed onto the aligner surface. Following Cupral treatment, a drastic decrease occurred in plaque thickness and matrix presence. As assessed by the CFU assay, total microbial load approached 10 9 CFUs/aligner, with slight differences in aerobiosis and anaerobiosis culture conditions; six macroscopically different types of colonies were detected and identified by matrix-assisted laser desorption ionization-time of flight mass spectrometry. Following Cupral treatment, microbial load dropped to undetectable levels, irrespectively of the conditions considered. Exposure of clear aligners to Cupral results in the elimination of contaminating microorganisms; the antimicrobial activity is retained up to 1.25% concentration. Overall, our data describe a novel use of Cupral, a copper–calcium–hydroxide-based compound, in daily hygiene practices with promising results.